Impact of exhaustive exercise on autonomic nervous system activity: insights from HRV analysis - Wang, W.; Shao, M.; Du, W.; Xu, Y. (Frontiers in Physiology, 2024)
Introduction: Exhaustive exercise is a common training method in sports, but its impact on the autonomic nervous system of the human body remains unclear. Understanding the effects of exhaustive exercise on the body and its connection with the autonomic nervous system and central nervous system is crucial for guiding healthy training methods.